Influence of silver ion reduction on electrical modulus parameters of solid polymer electrolyte based on chitosan-silver triflate electrolyte membrane (eXPRESS Polymer Letters)
The electric modulus properties of solid polymer electrolyte based on chitosan: AgCF3SO3 from 303 to 393 K have been investigated by using impedance spectroscopy. The shift of the M'' peak spectra with frequeny depends on the dissociation and association of ions. The lowest conductivity relaxation time τσ, was found for the sample with the highest conductivity. The real part of electrical modulus shows that the material is highly capacitive. The asymmetric peak of the imaginary part of electric modulus M'', predicts a non Debye type relaxation. The distribution of relaxation times was indicated by a deformed arc form of Argand plot. The increase of M' and M'' values above 358 K can be attributed to the transformation of silver ions to silver nanoparticles. The complex impedance plots and ultraviolet-visible (UV-vis) absorption spectroscopy indicate the temperature dependent of silver nanoparticles in chitosan-silver triflate solid electrolyte. The formation of silver nanoparticles was confirmed by transmission electron microscopy (TEM). The scaling behavior of M'' spectra shows that the dynamical relaxation processes is temperature independent for aparticular composition. The β exponent value indicate that the conductivity relaxation is highly non exponential.